The foundations of panning and developing parks and green areas at the city level (Damascus University Journal for engineering sciences, 2024)
Parks and green areas are considered the lungs of the city, So that, recent studies have clarified the various roles that they play and highlighted their role in improving the quality of life of their residents for their physical and psychological health. However, some large cities still suffer from a decrease in the proportion of areas allocated to them, especially in the old and slum residential neighborhoods, and with high population densities neighborhoods.This research aims to emphasize the role played by green spaces within the urban fabric, the priority of attention to their planning and development. It also aims to analyze the mechanisms of planning green areas, especially in the city of Aleppo.Through this, it deals with the criteria for planning quantitative and qualitative parks and the theoretical foundations for them according to the needs of individuals. The case study in the city of Aleppo.
Keywords: parks and green areas; park planning standars; foundations of park planning; green areas in aleppo